Virtual Launch of the Breakthrough Agenda Report 2024 - International Energy Agency; UN Climate Change (International Energy Agency, 2024)
The Breakthrough Agenda Report 2024 assesses the impact of international collaboration in accelerating the transition to clean energy technologies and sustainable solutions in key sectors. It was prepared by the International Energy Agency in collaboration with the UN Climate Change High-Level Action Champions Team at the request of world leaders.